2008
DOI: 10.1080/00220380801980798
|View full text |Cite
|
Sign up to set email alerts
|

Formal and Informal Rural Credit in Four Provinces of Vietnam

Abstract: This paper uses a survey of 932 rural households to uncover how the rural credit market operates in Vietnam. Households obtain credit through formal and informal lenders. Formal loans are almost entirely for production and asset accumulation, while informal loans are used for consumption smoothening. The determinants of formal and informal credit demand are distinct. While credit rationing depends on education and credit history, in particular, regional differences in the demand for credit are striking. A 'one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
185
3
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(231 citation statements)
references
References 15 publications
31
185
3
12
Order By: Relevance
“…Accordingly, preferential credit has been found to be inefficient in reducing poverty and improving agricultural growth. In another major study, Barslund and Tarp (2008) reported that a "one size fits all" method to scaling up preferential credit is not going to be the most advantageous. The expansion of preferential credit requires careful consideration for the need for credit in areas where access is presently low.…”
Section: Income Impact Of Different Credit Sources On Accessed Househmentioning
confidence: 99%
“…Accordingly, preferential credit has been found to be inefficient in reducing poverty and improving agricultural growth. In another major study, Barslund and Tarp (2008) reported that a "one size fits all" method to scaling up preferential credit is not going to be the most advantageous. The expansion of preferential credit requires careful consideration for the need for credit in areas where access is presently low.…”
Section: Income Impact Of Different Credit Sources On Accessed Househmentioning
confidence: 99%
“…Many researches find that credit may relax financial constraint via providing the poor with a source of capital for production or business activities. Evidence from empirical studies documents that credit significantly increases income of the poor households (Morduch and Haley, 2001;Barslund and Tarp, 2008). However, some studies argue that rural credit does not have the effect on income improvement in short term (Takahashi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These two banks aim at agriculture and rural development and poverty reduction. Formal credit is essential for agricultural development because it not only gives solution to the failures of rural financial markets, but also is an important factor in promoting production and generating income (Atieno, 1997;Barslund and Tarp, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nghiem et al (2012), using a quasi-experimental study on households of microfinance programs by NGOs, however find that there is no significant impact of participation on household welfare proxied by income and consumption per adult equivalent. Other papers focus on the demand for credit or credit rationing, such as Pham and Izumida (2002) and on the use of credit such as Barsland and Tarp (2008) who find that formal credit is used mostly for production and asset accumulation while formal credit is for consumption smoothing.…”
Section: Introductionmentioning
confidence: 99%